An epidemiological study of blood pressure and its relation with anthropometric measurements among schoolboys of Burdwan Municipal Area, West Bengal - Kaushik Nag; Nabarun Karmakar; Indranil Saha; Samir Dasgupta; Bijay Prasad Mukhopadhyay; Md Rafiul Islam Mondal (Wolters Kluwer Medknow Publications, 2018)
Background: High blood pressure (BP) is often an underdiagnosed problem, because of the asymptomatic nature in early phases of onset during adolescence. This increases the chances of developing complications later during adult life. Objective: The objective of this study was to find the relationship of BP with anthropometric measurements among school-going adolescent boys. Materials and Methods: It was a cross-sectional study conducted among 894 adolescent schoolboys aged 13 to 18 years from July 2013 to October 2014 in schools of Burdwan Municipal area, West Bengal. The required number of students from each school was determined by proportional probability sampling. Then, the required number of students from each school was selected by systematic random sampling technique. BP and anthropometric measurements such as weight, height, and waist circumference were done using standard guidelines. Results: The mean systolic and mean diastolic BP in the study participants was significantly higher with an increase in weight, height, waist circumference, and body mass index (BMI) (P < 0.05). BP was found to be positively correlated with different anthropometric measurements such as weight, height, waist circumference, and BMI, which were statistically significant. Conclusion: Early detection of high BP and application of lifestyle modification among adolescents will be helpful in reducing the burden of high BP in adult life.